2012
DOI: 10.1089/ast.2011.0704
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen and Hydrogen Peroxide in the Early Evolution of Life on Earth:In silicoComparative Analysis of Biochemical Pathways

Abstract: In the Universe, oxygen is the third most widespread element, while on Earth it is the most abundant one. Moreover, oxygen is a major constituent of all biopolymers fundamental to living organisms. Besides O 2 , reactive oxygen species (ROS), among them hydrogen peroxide (H 2 O 2 ), are also important reactants in the present aerobic metabolism. According to a widely accepted hypothesis, aerobic metabolism and many other reactions/pathways involving O 2 appeared after the evolution of oxygenic photosynthesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 57 publications
1
60
0
Order By: Relevance
“…Hydrogen peroxide (H 2 O 2 ) is a central reactive oxygen species (ROS) in the global cycle of oxygen (O 2 ), and is thought to have been a precursor to O 2 via abiotic reactions in early Earth (Slesak et al, 2012). ROS such as H 2 O 2 and superoxide (O…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen peroxide (H 2 O 2 ) is a central reactive oxygen species (ROS) in the global cycle of oxygen (O 2 ), and is thought to have been a precursor to O 2 via abiotic reactions in early Earth (Slesak et al, 2012). ROS such as H 2 O 2 and superoxide (O…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in modern anaerobes, components of aerobic respiration, and EAS, such as various cytochrome oxidases (Baughn and Malamy, 2004;Das et al, 2005;Dolla et al, 2006), NADH oxidases (Yang and Ma, 2007), SODs (Gregory et al, 1978;Dos Santos et al, 2000;Brioukhanov and Netrusov, 2004;Dolla et al, 2006;Horne and Lessner, 2013), SORs (Niviére and Fontecave, 2004;Dolla et al, 2006), and CATs (Brioukhanov and Netrusov, 2004;Dolla et al, 2006;Mishra and Imlay, 2013) have been identified previously. According to other reports, enzymes and metabolic pathways that are directly or indirectly oxygendependent are present in many anaerobes (Peregrin-Alvarez et al, 2003;Freitas et al, 2005;Raymond and Segrè, 2006;Passardi et al, 2007;Ś lesak et al, 2012). Moreover, according to theoretical studies, Fe/MnSOD and CAT would have been required for basic metabolism of the hypothetical LUCA (Ouzounis et al, 2006).…”
Section: Modern Anaerobesmentioning
confidence: 96%
“…Data collected during the Viking missions showed that the surface of Mars was highly oxidized compared to the Mars atmosphere [13]. Mapping of hydrogen peroxide (H 2 O 2 ) on Mars using infrared high-resolution imaging spectroscopy indicated H 2 O 2 abundance on Mars is 15 ± 10 ppb although prior mapping showed concentrations as high as 40 ppb [14].…”
Section: The Martian Environmentmentioning
confidence: 99%
“…Data from the Viking missions showed that the surface of Mars was highly oxidized compared to its atmosphere [13]. Additional studies of Mars have shown that H 2 O 2 abundance can range from 15 ± 10 ppb to 40 ppb [14].…”
Section: Exposure To An Oxidative Environmentmentioning
confidence: 99%